2022
DOI: 10.1117/1.oe.61.9.093107
|View full text |Cite
|
Sign up to set email alerts
|

Hformer: Hybrid convolutional neural network transformer network for fringe order prediction in phase unwrapping of fringe projection

Abstract: Deep learning based on convolutional neural network (CNN) has attracted more and more attention in phase unwrapping of fringe projection three-dimensional (3D) measurement. However, due to the inherent limitations of convolutional operator, it is difficult to accurately determine the fringe order in wrapped phase patterns that rely on continuity and globality.To attack this problem, in this paper we develop a hybrid CNN-transformer model (Hformer) dedicated to phase unwrapping via fringe order prediction. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Moreover, the rapid ascendancy of the model structure was particularly evident in the domain of natural language processing (NLP) following the breakthrough performance of bidirectional encoder representations from transformers (BERT) as demonstrated by Devlin et al 5 The dominance of BERT across a spectrum of NLP tasks validated the potency of the transformer architecture, solidifying its position as a cornerstone in the evolution of NLP methodologies. Inspired by its capabilities, researchers have found that the transformer structure also performs well in computer vision tasks, and transformers are playing powerful roles as emerging research frameworks during the more than a decade of dominance by convolutional neural networks (CNNs) in the vision domain 6 …”
Section: Deep Learning- and Transformer-related Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the rapid ascendancy of the model structure was particularly evident in the domain of natural language processing (NLP) following the breakthrough performance of bidirectional encoder representations from transformers (BERT) as demonstrated by Devlin et al 5 The dominance of BERT across a spectrum of NLP tasks validated the potency of the transformer architecture, solidifying its position as a cornerstone in the evolution of NLP methodologies. Inspired by its capabilities, researchers have found that the transformer structure also performs well in computer vision tasks, and transformers are playing powerful roles as emerging research frameworks during the more than a decade of dominance by convolutional neural networks (CNNs) in the vision domain 6 …”
Section: Deep Learning- and Transformer-related Researchmentioning
confidence: 99%
“…Inspired by its capabilities, researchers have found that the transformer structure also performs well in computer vision tasks, and transformers are playing powerful roles as emerging research frameworks during the more than a decade of dominance by convolutional neural networks (CNNs) in the vision domain. 6…”
Section: Deep Learning-and Transformer-related Researchmentioning
confidence: 99%
“…In addition, neural networks are also widely used in the field of 3D measurement of moving objects. [29][30][31] Qian et al 32 used geometric constraints and phase unwrapping supported by deep learning to obtain object phases from a single fringe and eliminate motion artifacts. Yu et al 33 used deep learning phase retrieval techniques for dynamic 3D measurement.…”
Section: Introductionmentioning
confidence: 99%
“…used CNN to analyze the 3D profiles of objects from a single fringe pattern. In addition, neural networks are also widely used in the field of 3D measurement of moving objects 29 31 Qian et al 32 .…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al [26] have proposed a hybrid model 'Hformer' based on Cross Attention Transformer (CAT) and a type of CNN called High Resolution Network (HRNet) for phase unwrapping in fringe projection. In this model, input phase is fed to HRNet followed by Encoder Decoder network with CAT as building blocks.…”
Section: Introductionmentioning
confidence: 99%